A vezetői elégedettség vizsgálata egy mezőgazdasági szervezetben - Barta, Ágnes (Acta Agraria Debreceniensis, 2002)
Human resource managers are able to plan and organise activities which influence their own and other peoples’ performance, and also make necessary corrections on the basis of those performances. Managerial skills, experience, type of abilities and competencies each play a definitive role in organisational decisions. On the other hand, the second determinative factor of managerial performance is the organisation in witch they work. The goal of my survey was to analyse contentment of different level managers at Szerencsi Agricultural Rt.